2014
DOI: 10.14245/kjs.2014.11.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Does Obesity Make an Influence on Surgical Outcomes Following Lumbar Microdiscectomy?

Abstract: ObjectiveThe purpose of this study was to evaluate the effect of patients' bod mass index (BMI) on surgical outcomes following one-level lumbar microdiscectomy.MethodsFrom June 2003 to March 2007, 129 patients underwent one-level lumbar microdiscectomy performed at a single institution. We divided the patients into 3 groups, depending on BMI. A retrospective study was conducted among the 3 groups. The operation time, estimated blood loss (EBL), postoperative hospital day, recurrent disc herniation, intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
3
6
1
1
Order By: Relevance
“…169 One Korean study showed that obesity did not affect surgical outcomes following lumbar microdiscectomy. 170 In at least 1 study, investigators suggested this may be due to patient noncompliance. 31 These studies highlight a need for a better understanding of the available treatment options and the development of new approaches to the simultaneous treatment of obesity and pain, such as with pharmacologic options.…”
Section: Headachesmentioning
confidence: 99%
“…169 One Korean study showed that obesity did not affect surgical outcomes following lumbar microdiscectomy. 170 In at least 1 study, investigators suggested this may be due to patient noncompliance. 31 These studies highlight a need for a better understanding of the available treatment options and the development of new approaches to the simultaneous treatment of obesity and pain, such as with pharmacologic options.…”
Section: Headachesmentioning
confidence: 99%
“…Reherniated lumbar is an important disease which seen commonly. The rate of recurrent disc herniation after lumbar discectomy is 5% to 15% [5]. So that, recurrent lumbar disc herniation (RLDH) is a major cause of surgical failure [7], the recurrent disc herniation is the major cause of the failed back surgery syndrome [8].…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons choose simple discectomy again, while some surgeons advocate fusion surgery. Because recurrent disectomy (ipsilateral/contralateral) requires more disc and posterior spinal component removal (lamina and/or facet joint), recurrent discectomy will increase the likelihood of segmental instability and due to scar tissue; dural tear, and nerve injuries may be greater at simple re-discectomies, some surgeons suggest fusion surgery at first recurrent, regardless of whether instability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Отношение к ожирению как фактору риска рецидива ГМД неоднозначно: по некоторым данным, ожирениезначимый фактор риска рецидива, однако по другимнет [10][11][12]. Выполнение кюретажа диска в дополнение к секвестрэктомии снижает риск рецидива ГМД на 3%.…”
Section: рецидив гмдunclassified